DEFERRED TAX EXPENSES AS EARNING MANAGEMENT INDICATOR - Louis Yosen Primsa Tarigan (Journal of Accounting and Management Innovation, 2019)
The aim of this study is to examine the benefit of using deferred tax expenses to detect the practice of earning management. Data source are secondary data from www.idx.co.id. The data is gathered for automotive companies for the year 2012 until and including 2017. In order to optimally perform the statistical analysis, the data first needs to meet certain requirements. These requirements are: the data is normal distributed, possible outliers in the data are removed, the data is assessed for multicollinearity, and finally, the data needs to be assessed for heteroscedasticity. We find that the deferred tax expenses influence earning management to avoid loss and to avoid earning decline.Keywords earning management; deferred tax expenses